El Viraje Político-cultural del Comunismo Argentino en Tiempos de Realismo Socialista y Frentes Populares - Piemonte, Víctor Augusto (2013)
The political-cultural doctrine of socialist realismwas approved by the Communist Party of the Soviet Union and incorporated into the official policy of the Soviet government in 1934 after the completion of the First Congress of Soviet Writers. It established the methodological and aesthetic parameters which should guide all artistic production within the Soviet Union. Thereafter, any possibility of relative independence of culture and art in relation to official policy was severely questioned. This subordination position occurred at a time when the Third International began to abandon the class against class tactic in order to turn to the formation of popular fronts, thus generating significant effects in the process of building a proletarian culture. The aim of this study is to investigate the impact of this relationship between cultural policy and politics itself, as evidenced by the connection between socialist realismand a political shift in the type of cultural projects carried out inside the Communist Party of Argentina (PCA) for the proletariat of their country by the middle of the 1930s. To this end, we analyze how PCA assumed that culture could be converted from being a tool of class war into a tool for democratic freedom in the struggle against reactionary authoritarianism.